Financial globalization and wage inequality. (27th July 2022) - Pi, Jiancai; Zhang, Kaiqi; Huang, Xiangyu
Abstract: This paper analyzes how financial globalization affects skilled‐unskilled wage inequality. We treat financial globalization as more regions being integrated into the global financial market. We find that a higher degree of financial globalization will decrease skilled‐unskilled wage inequality if it induces a small increase in the capital tax rate. However, a higher degree of financial globalization will increase skilled‐unskilled wage inequality if it induces a big increase in the capital tax rate.